Car parking provision analysis based on the land use types for Malaysian towns - Awang, Mohd. Noor (UTM, 2003)
The growth of both urban functions and the number of population who own and use motor vehicles in their daily activities has increased the demand for vehicle parking spaces for all categories of land uses. These growth, together with the increase in density and intensity of developments such, as residential, industrial and commercial land uses, make the existing parking guidelines and parking standards for all Malaysian cities obsolete. As parking demand and parking requirements change very fast, this study looks into the approaches and methods which have been used in other cities in their works in revising their parking guidelines and standards to suit the current situation within their context. These cities are Singapore, Santa Clarita (USA), Hong Kong and the Gold Coast (Australia). The existing parking guidelines and standard for a number of Malaysian towns i.e. Johor Bahru, Seremban, Shah Alam, Melaka and Taiping have been examined for their suitability to the current situation and it was discovered that they were insufficient and no longer suitable. The actual demand for parking spaces for a number of towns were surveyed and the results show that these towns experienced acute shortage of parking spaces for certain categories of land uses, especially for offices and commercial areas. The study recognizes the complexity of parking provision because the demand for parking spaces very much depends on the level of economic development of a particular town. The parking guidelines and parking standards proposed by this study has included some new standards for certain types of land uses such as golf courses, public libraries, hospitals, condominiums and town houses. Apart from proposing the increase in parking provision for certain types of land use, the study also suggests the overall improvements in parking guidelines and in parking provision. The concept of shared parking for commercial and services land uses is expected to result in optimum utilisation of parking spaces. Mechanical parking would be more suitable for older parts of the city, which are normally characterised by the lack of space, as the system will relatively occupy smaller land area to accommodate the same number of parking lots compared to conventional types of parking systems. The new approach proposed by this study is the use of modal split model by the local planning authority in assessing parking space requirement. On-street parking are discouraged in most parts of the city, but a limited very short term parking should be allowed only in certain areas. The provision of heavy vehicle parking spaces near residential and industrial areas are expected to solve problems related to road safety and the environment. Examples of layouts, lot sizes and the concept of landscape for parking areas are provided for easy reference by the local authority. Parking facilities with special design for disabled are included in the proposed guidelines and standards.